Design of a 377 Ω Patch Antenna for Ambient RF Energy Harvesting at Downlink Frequency of GSM 900 - Devi, K. K. A.; Sadasivam, S.; Md.Din, Norashidah; Chakrabarthy, C. K. (IEEE, 2011)
A novel 377 Ω patch antenna operating at GSM 900 downlink band for RF energy harvesting is proposed and analyzed in this paper. The designed antenna consists of a normal patch with two steps incorporated at the appropriate position to enhance its bandwidth. The antenna is designed and tested in Agilent advance design systems ADS environment and constructed on a FR4 substrate. The antenna yields an impedance bandwidth of 34.35% (325 MHz) at 946 MHz centre frequency with a return loss S11 of -29.22dB and gain of 5.2 dBi. The proposed patch antenna is suitable for ambient RF energy harvesting at downlink frequency band of GSM 900 as demonstrated by simulation and experimental results. The measured results closely agree with the simulated results.